2016
DOI: 10.12944/crnfsj.4.special-issue-october.21
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Α- and Β-Thujone in Wormwood and Sage Infusions of Greek Flora and Estimation of their Average Toxicity

Abstract: Artemisia absinthium (wormwood) and Salvia sp. (sage) are used as additives to pharmaceuticals, food and alcoholic beverages while in Greece both herbs are also consumed as infusions. The compounds α- and β-thujone, are monoterpenes, which are found in various preparations of these herbs. According to organizations (EMA, SCF) and clinical studies, α- and β-thujone have shown neurotoxic effects in humans over established limits. In this study wormwoodandsageinfusions were investigated in terms of the relative %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 20 publications
3
14
1
1
Order By: Relevance
“…A. absinthium contains thujone, and when consumed in large doses, along with large quantities of alcohol, can induce convulsions. GC‐MS is a widely used method to detect and differentiate drug analytes and has been used to identify and quantitate α‐ and β‐thujone . However, unlike DNA typing methods, GC‐MS cannot determine the source of the thujone, sage ( Salvia officinalis ), or wormwood .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A. absinthium contains thujone, and when consumed in large doses, along with large quantities of alcohol, can induce convulsions. GC‐MS is a widely used method to detect and differentiate drug analytes and has been used to identify and quantitate α‐ and β‐thujone . However, unlike DNA typing methods, GC‐MS cannot determine the source of the thujone, sage ( Salvia officinalis ), or wormwood .…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who frequently ingested absinthe would experience epileptic‐like episodes. Originally thought to act on the same receptors as tetrahydrocannabinol (THC), researchers later realized that the two components of wormwood are α‐thujone and more prominently, β‐thujone, which block the gamma‐aminobutyric acid (GABA) receptors in the brain, causing convulsions in high doses . Researchers have shown that thujone alone was not responsible in this absinthism effect and that higher levels of alcohol at the time might have increased the effects of thujone in an individual .…”
mentioning
confidence: 99%
See 3 more Smart Citations